Microbiological profile of community acquired pneumonia in diabetic patients and their antibiotic sensitivity pattern in a tertiary care hospital of Bangladesh (BIRDEM Medical Journal, 2024)
Background: Diabetes mellitus is an immunosuppressive state leading to increased susceptibility to various infections. Pneumonia, urinary tract infection, skin and soft tissue infection are more common in diabetic population. Pneumonia in diabetic patient is often atypical, caused by more virulent organisms and associated with increased antibiotic resistance. The predisposition for infection may also be based on conditions that interfere with normal clearance mechanisms and on disturbance of pulmonary immune cell function. Several aspects of immunity such as polymorphonuclear leukocyte function (i.e. leukocyte adherence, chemotaxis and phagocytosis) and bactericidal activity of serum are depressed in patients with diabetes. This study was designed to evaluate the microorganisms most commonly causing community acquired pneumonia in diabetic patients.Methods: This descriptive type of cross-sectional study was conducted in Department of Medicine, BIRDEM General Hospital from 25th March 2018 to 24th September 2018. Total 50 diabetic patients with community acquired pneumonia were included. Detail demographic data were collected and recorded in structured case report form. Clinical examination and relevant investigation were done. Antibioctic sensitivity pattern of isolated organisms were studied.Results: Mean age of the patient was 53.4 ± 11.5 years. Male and female ratio was 1.6:1. In this study Klebsiella pneumoniae was found to be the most prevalent 14 (30.4%), followed by Streptococcus pneumoniae 11 (23.9%). Among the Gram-positive cocci, Streptococcus pneumonia 11 (23.9%) was the predominant, followed by Staphylococcus aureus in 6 (13.0%) patients. Bacterial antibiotic sensitivity pattern to ceftriaxone, ceftazidime, cefixime and amoxycillin were as follows: Klebsiella pneumonia (57.1%, 14.2%, 28.5%, 21.4% respectively), Streptococcus pneumonia (45.5%, 54.5%, 36.3%, 0% respectively). Present study shows that maximum patients (72.0%) were having uncontrolled glycemic status. In this study, most of the growth of all the bacteria (Klebsiella 64.2%, Staphylococcus 72.8%, Pseudomonas 60.0%, Acinetobacter 100%, E. coli 100%) occurred in patients with poor glycemic control (HbA1c  ³7.0%).Conclusions: This study results concluded that CAP in diabetic patients are more frequently due to Gram negative bacilli like Klebsiella pneumoniae, Pseudomonas and also Staphylococcus aureus and they are resistant to commonly used antibiotics. So, effective treatment of community acquired pneumonia in diabetic patients should be guided by sputum culture results.BIRDEM Med J 2024; 14(1): 10-15